Isolated theory of mind deficits and risk for frontotemporal dementia: a longitudinal pilot study. Issue 7 (1st November 2012) - Pardini, Matteo; Emberti Gialloreti, Leonardo; Mascolo, Maria; Benassi, Francesca; Abate, Lucia; Guida, Silvia; Viani, Erica; Dal Monte, Olga; Schintu, Selene; Krueger, Frank; Cocito, Leonardo
Abstract : Objective: Recent data suggest that theory of mind (ToM) deficits represent an early symptom of the behavioural variant of frontotemporal dementia (bvFTD). However, longitudinal data on the natural history of subjects presenting with isolated ToM deficits are lacking. The aim of the study was to verify if isolated ToM deficits represent an at-risk state for prefrontal dysfunction and bvFTD. Methods: A population of healthy subjects (n=4150, age range: 50–60 years) completed a clinical and neuropsychological evaluation including the Reading the Mind in the Eyes Test (RMET), a widely used ToM task. From this group, we recruited a low-RMET group (n=83) including subjects with RMET scores lower than 2 SDs but an otherwise normal neuropsychological evaluation and a control group. All subjects underwent evaluation at baseline and after 2 years. Results: Subjects in the low-RMET group showed decline in prefrontal functions at follow-up. Moreover, at follow-up 12 subjects in the low-RMET group presented with findings suggestive of bvFTD. Neuropsychological performance was stable in the control group. Conclusions: Our data suggest that isolated ToM deficits could represent an at-risk situation for the development of future prefrontal dysfunction and bvFTD. ToM evaluation should be included in neuropsychological protocols aimed to evaluate the early phases of dementia.